Microwave Assisted Synthesis of Arylpyrazoles Using Montmorillonite K-10 - Hatamjafari, Farhad (Asian Journal of Chemistry, 2012)
Montmorillonite K-10 clay catalyzed Friedlander condensation of Baylis-Hillman adducts with phenyl hydrazine hydrochloride afforded 1,5-diarylpyrazoles.